Żetony z piekarni Witalisa Dąbrowskiego w kolonii górniczej Reden - Czyżewski, Bartłomiej (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
For many years, tokens from Witalis Dąbrowski’s bakery have been incorrectly linked with Kielce. The aim of this article is to show that these tokens in fact were used in Reden (now a district of Dąbrowa Górnicza). Additionally, the author of the article, based on archival sources and newspapers of that time, tries to reconstruct the life and career of Witalis Dąbrowski.
Keywords: regional studies; region; Silesia; Poland; Czech Republic; Germany; regional journal; historical journal